2002
DOI: 10.1046/j.1365-8711.2002.05785.x
|View full text |Cite
|
Sign up to set email alerts
|

The population of the Galactic plane as seen by MSX

Abstract: The combination of mid-infrared data from the MSX satellite mission and groundbased near-infrared photometry is used to characterise the properties of the midinfrared population of the Galactic plane. The colours of the youngest sources still heavily embedded within their natal molecular clouds are in general different from evolved stars shrouded within their own dust shells. Our main motivation is to use MSX for an unbiased search for a large (∼ 1000) sample of massive young stellar objects (MYSOs). A simple … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
247
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(268 citation statements)
references
References 60 publications
(89 reference statements)
16
247
0
5
Order By: Relevance
“…Maser-hosting sources are in general more massive and hotter than sources showing 1.2 mm continuum emission but no maser. Also, sources hosting methanol maser show hot core characteristics and most of them pass the Lumsden MSX criterion for massive protostars in the Galactic plane (Lumsden et al 2002). Finally, methanol masers have been detected toward dark mid-IR clouds, clearly indicating that star formation is ongoing in those regions.…”
Section: Introductionmentioning
confidence: 86%
“…Maser-hosting sources are in general more massive and hotter than sources showing 1.2 mm continuum emission but no maser. Also, sources hosting methanol maser show hot core characteristics and most of them pass the Lumsden MSX criterion for massive protostars in the Galactic plane (Lumsden et al 2002). Finally, methanol masers have been detected toward dark mid-IR clouds, clearly indicating that star formation is ongoing in those regions.…”
Section: Introductionmentioning
confidence: 86%
“…While various samples of high-mass proto-stellar objects have been defined based on various criteria, such as maser emission (e.g., Walsh et al 1997;Pestalozzi et al 2005) and infrared (IR) colors (Palla et al 1991;Molinari et al 1996;Sridharan et al 2002;Lumsden et al 2002;Robitaille et al 2008), an unbiased sample has not yet been assembled. Much effort has focused on follow-up studies of bright IR sources detected by the Infrared Astronomy Satellite (IRAS) and showing far-infrared (FIR) colors typical of ultra-compact H ii regions (Wood & Churchwell 1989), e.g., in high-density molecular tracers (Bronfman et al 1996;Molinari et al 1996), dust continuum emission , or maser emission (e.g., Palla et al 1993;Beuther et al 2002).…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…We refer here to the diagrams shown in Figs. 3, 4, 9 and 10 in Lumsden et al (2002) as L1, L2, L3 and L4, respectively. In each of these diagrams we defined a line along the reddening vector which limits the zone where most of the known PNe in the diagrams are We studied the locations of our candidates, symbiotic stars, T-Tauri and post-AGB stars in the diagrams L1, L2, L3 and L4 and found that all of them separate PNe from T-Tauri and symbiotic stars quite nicely.…”
Section: Msx + 2mass Infrared Diagramsmentioning
confidence: 99%